Autoimmune cytopenias in chronic lymphocytic leukemia. Issue 11 (7th July 2014) - Visco, Carlo; Barcellini, Wilma; Maura, Francesco; Neri, Antonino; Cortelezzi, Agostino; Rodeghiero, Francesco
<x xml:space="preserve">Abstract</x> Chronic lymphocytic leukemia (CLL) is frequently complicated by secondary autoimmune cytopenias (AIC) represented by autoimmune hemolytic anemia (AIHA), immune thrombocytopenia (ITP), pure red cell aplasia, and autoimmune granulocytopenia. The distinction of immune cytopenias from cytopenias due to bone marrow infiltration, usually associated with a worse outcome and often requiring a different treatment, is mandatory. AIHA and ITP are more frequently found in patients with unfavorable biological risk factors for CLL. AIC secondary to CLL respond less favorably to standard treatments than their primary forms, and treating the underlying CLL with chemotherapy or monoclonal antibodies may ultimately be necessary. Am. J. Hematol. 89:1055–1062, 2014. © 2014 Wiley Periodicals, Inc.